Monitoring of active layer dynamics at a permafrost site on Svalbard using multi-channel ground-penetrating radar - Westermann, Sebastian; Wollschläger, Ute; Boike, Julia (The Cryosphere, 2010)
Multi-channel ground-penetrating radar is used to investigate the late-summer evolution of the thaw depth and the average soil water content of the thawed active layer at a high-arctic continuous permafrost site on Svalbard, Norway. Between mid of August and mid of September 2008, five surveys have been conducted in gravelly soil over transect lengths of 130 and 175 m each. The maximum thaw depths range from 1.6 m to 2.0 m, so that they are among the deepest thaw depths recorded in sediments on Svalbard so far. The thaw depths increase by approximately 0.2 m between mid of August and beginning of September and subsequently remain constant until mid of September. The thaw rates are approximately constant over the entire length of the transects within the measurement accuracy of about 5 to 10 cm. The average volumetric soil water content of the thawed soil varies between 0.18 and 0.27 along the investigated transects. While the measurements do not show significant changes in soil water content over the first four weeks of the study, strong precipitation causes an increase in average soil water content of up to 0.04 during the last week. These values are in good agreement with evapotranspiration and precipitation rates measured in the vicinity of the the study site. While we cannot provide conclusive reasons for the detected spatial variability of the thaw depth at the study site, our measurements show that thaw depth and average soil water content are not directly correlated. - - The study demonstrates the potential of multi-channel ground-penetrating radar for mapping thaw depth in permafrost areas. The novel non-invasive technique is particularly useful when the thaw depth exceeds 1.5 m, so that it is hardly accessible by manual probing. In addition, multi-channel ground-penetrating radar holds potential for mapping the latent heat content of the active layer and for estimating weekly to monthly averages of the ground heat flux during the thaw period.
Gesehen am 29.11.2023